Ba0.5Gd0.8La0.7Co2O6-δ Infiltrated in Porous BaZr0.7Ce0.2Y0.1O3 Backbones as Electrode Material for Proton Ceramic Electrolytes. Issue 4 (1st January 2017) - Strandbakke, Ragnar; Vøllestad, Einar; Robinson, Shay A.; Fontaine, Marie-Laure; Norby, Truls
Abstract : Several porous backbone layers of proton conducting BaZr1-x-y Cex Yy O3-δ (BZCY) were prepared by spray-coating or painting on BaZr0.7 Ce0.2 Y0.1 O2.95 (BZCY72) button cells followed by high temperature firing in air. This step enabled to produce ceramic backbones with various grain and pore sizes. The backbones were further infiltrated with mixed conducting double perovskite Ba0.5 Gd0.8 La0.7 Co2 O6-δ (BGLC587) suspensions and annealed in air. The resulting composite layers were tested as oxygen/steam side electrodes for proton ceramic fuel cells and electrolysers (PCFCs-PCEs). The results confirm that a high performing electrode material such as BGLC587 with partial proton conductivity and high thermal expansion can be applied on a proton conducting electrolyte with low thermal expansion by use of backbone infiltration without losing electrochemical functionality. Indeed, the electrodes display an apparent polarization resistance of only 0.03 Ω cm 2 at 700°C in oxygen humidified with 2.7% H2 O. We further extracted and parameterized the impedances associated with the charge and mass transfer reactions in a system where protons are the dominating charge carriers at intermediate to low temperatures and oxide ions dominate the overall transport at high temperature. The fitting revealed to what extent the charge and mass transfer reactions are short-circuited by electronic leak current across the sample at high temperatures and p O2 's. The acquired activation energies and pre-exponential values were used to explain materials-specific and micro-structural differences between the different electrode architectures.